Melting heat transport analysis for bioconvective rheological nanofluid flow subject to gyrotactic microorganism's - Hassan Ali Ghazwani (Case Studies in Thermal Engineering)
Two dimensional steady bioconvection Oldroyd-B nanomaterial flow due to stretchable sheet. Suspension of both nanoparticles and gyrotactic microorganism are addressed. Melting boundary conditions are imposed. Energy equation is assisted with joule heating, thermophoretic diffusion, thermal radiation and Brownian motion. Further thermo-diffusion and diffusion thermo impacts are considered. Related expressions of flow model are transformed through appropriate similarity variables. Convergent series solutions are developed by employing homotopic technique. Convergence regions of solutions are discussed. Graphical results illustrate the impact of sundry variables (melting parameter, magnetic parameter, Dufour number, bioconvection Lewis number, thermophoresis variable, Soret number, radiation parameter, Brownian motion variable, Peclet number and various other interesting parameters) on flow behavior are analyzed. microorganism's field shows a decaying trend for higher melting and bioconvection Lewis number. Concentration and liquid flow have reverse impact for melting heat variable. Thermal distribution increased against higher random motion variable, whereas reverse effect noticed for melting heat variable.